Evaluation of image quality and dose reduction of 80 kVp neck computed tomography in patients with suspected peritonsillar abscess. Issue 8 (August 2015) - Scholtz, J.-E.; Hüsers, K.; Kaup, M.; Albrecht, M.H.; Beeres, M.; Bauer, R.W.; Schulz, B.; Vogl, T.J.; Wichmann, J.L.
<x xml:space="preserve">Abstract</x> Aim To evaluate neck computed tomography (CT) with a reduced tube voltage of 80 kVp in patients with suspected peritonsillar abscess (PTA) regarding objective and subjective image quality, and the potential for dose reduction. Materials and methods Forty-seven patients with clinically suspected PTA were retrospectively analysed. Patients were examined using dual-source CT in dual-energy mode. The objective and subjective image quality of 80 kVp images were compared with linearly blended 120 kVp images (M_0.3; 30% of 80 kV, 70% of 140 kV spectrum). Attenuation of abscess rim enhancement, central necrosis, and several other anatomical landmarks were measured. The signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR), and rim-to-abscess CNR (raCNR) were calculated. Radiation dose was assessed as size-specific dose estimates (SSDE). Subjective image quality was assessed according to the European guidelines on quality criteria for CT. Interobserver agreement was calculated using the intraclass correlation coefficient (ICC). Results Attenuation of inflamed soft tissue (141.7 ± 16.3 versus 93.7 ± 9.3 HU, p < 0.001), CNR (9.6 ± 4.8 versus 5.6 ± 3.8, p = 0.001), raCNR (14.3 ± 5.9 versus 12.4 ± 4.4, p = 0.02), and subjective image sharpness (3.6 ± 0.6 versus 2.8 ± 0.7, p < 0.001) were significantly increased in the 80 kVp compared to 120 kVp, whereas subjective and objective image noise were significantly increased with 80 kVp acquisition (p < 0.001). Overall interobserver agreement was almost perfect (ICC, 0.87). Calculated SSDE of 80 kVp acquisition was decreased by 49.7% compared to 120 kVp (10.58 ± 0.76 versus 21.04 ± 1.43 mGy, p < 0.001). Conclusion Low-tube-voltage 80 kVp neck CT provides increased enhancement of soft-tissue inflammation, CNR, raCNR, and improved abscess delineation in patients with PTA compared to standard 120 kVp acquisition while resulting in a significant reduction of radiation exposure.